2009
DOI: 10.1007/s10552-009-9383-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tumor stage, symptoms, and time of blood draw on serum concentrations of organochlorine compounds in exocrine pancreatic cancer

Abstract: Restriction or adjustment by stage and timing of blood draw may be insufficient to prevent biases associated with cancer progression. Symptoms may enable investigators to assess disease-induced changes in lipophilic exposure biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…This assumption following Philips et al (1989) and Porta et al (2009b) was held for monitored populations, considering they revealed not significant changes in lipid concentrations during the monitoring study. The obtained results of our monitored samples are presented in table I.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…This assumption following Philips et al (1989) and Porta et al (2009b) was held for monitored populations, considering they revealed not significant changes in lipid concentrations during the monitoring study. The obtained results of our monitored samples are presented in table I.…”
Section: Resultsmentioning
confidence: 80%
“…Concentrations of organochlorine pesticides are in a state of equilibrium between blood serum and adipose tissue or other lipid-rich tissues (Phillips et al 1989, Porta et al 2009b). This assumption following Philips et al (1989) and Porta et al (2009b) was held for monitored populations, considering they revealed not significant changes in lipid concentrations during the monitoring study.…”
Section: Resultsmentioning
confidence: 99%
“…*The reference category for all models includes groups 1 to 4 of ISCO 88.†All models are adjusted for age, sex, tumour stage and cholestatic syndrome 27 29

Regression coefficient.

…”
Section: Methodsmentioning
confidence: 99%
“…The following items should be reported: 1) the setting of the biological sample collection (place, time of the day, time of the year, laboratories involved, personnel involved, etc); 2) amount/volume/size of sample(s); 3) nature of the collecting procedure (anticoagulant involved, e.g., heparin, EDTA) 4) if the participant is healthy, participant condition at the sample collection (fasting status, position, etc) when appropriate; 5) if participants are not healthy individuals in stable physiological conditions, then report the relevant aspects of the health status and clinical conditions of the participants24 25; 6) in all instances, consider reporting the time between sample collection and relevant clinical or physiological endpoints that might have affected the characteristics or concentrations of the biomarker 26. In particular, report any relevant characteristic of the participants which might influence the biomarker levels in any known or unknown way.…”
Section: Checklist Of Itemsmentioning
confidence: 99%